Brewer's spent yeast improves human gut microbiota and ameliorates clinical blood parameters: A randomized, double-blind, placebo-controlled trial - Horn, Priscila Aparecida; Zeni, Ana Lúcia Bertarello; Herkenhoff, Marcos Edgar [UNESP]; Curbani, Luana; Pereira Gonçalves, Gustavo Henrique; Rutkoski, Camila Fatima; Israel, Nicole Grasmuk; de Almeida, Eduardo Alves (Elsevier, 2024)
This study investigated the effects of Brewer's spent yeast (BSY) on blood clinical parameters, changes in the intestinal production of short-chain fatty acids, and microbiota composition. A double-blind, placebo-controlled, randomized clinical trial intervention study was conducted on 50 healthy volunteers for four weeks, in which participants took a pill containing 500 mg of BSY or an equivalent placebo pill containing maltodextrin. After the intervention, plasma total cholesterol level decreased, and fecal short-chain fatty acids in the form of butyric acid and acetic acid increased in the BSY group but not in the control group. Microbiome analysis by qPCR showed a higher abundance of healthy associations of Lactobacillus and Firmicutes in the BSY-T group, suggesting that the dietary metabolic response may depend on the specific composition of the gut microbiota. These results indicate the potential positive impact of Brewer's yeast on metabolic health and intestinal microbiota.
Keywords: Brewer's spent yeast; Cholesterol; Clinical trial; Glucans; Gut microbiota; Healthy humans; Prebiotic; Randomized; Short chain fatty acids